2017
DOI: 10.1091/mbc.e16-06-0381
|View full text |Cite
|
Sign up to set email alerts
|

UNC-45A is required for neurite extension via controlling NMII activation

Abstract: UNC-45A is a novel regulator of neuronal differentiation. UNC-45A localizes at the growth cone, binds to NMIIA and NMIIB, and is disposable for neuronal survival but is required for neurite initiation and extension via regulating NMII activation. Thus UNC-45A is a potential master regulator of a number of NMII-mediated cellular processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…Most of the studies published so far on the mammalian isoform UNC-45A have focused on its role as direct or indirect regulator of actomyosin contractility. This includes studies from our laboratories showing that UNC-45A co-localizes with NMII in mammalian cells including cancer cells, NK cells and neurons [17,19,20]. This also includes a study from Dr. Lappalainen's group showing that the UCS domain of UNC-45A co-localizes with stress fibers in the U2OS cell line where it promotes myosin folding and stress fibers assembly [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the studies published so far on the mammalian isoform UNC-45A have focused on its role as direct or indirect regulator of actomyosin contractility. This includes studies from our laboratories showing that UNC-45A co-localizes with NMII in mammalian cells including cancer cells, NK cells and neurons [17,19,20]. This also includes a study from Dr. Lappalainen's group showing that the UCS domain of UNC-45A co-localizes with stress fibers in the U2OS cell line where it promotes myosin folding and stress fibers assembly [6].…”
Section: Discussionmentioning
confidence: 99%
“…Third, fixation methods other than cold methanol (which we have used here and previously to show that UNC-45A is a MAP [5]) may not be suitable for MT localization or co-localization studies because their either do not preserve MTs well, or interfere with antigen binding. With regards to this point, our work on co-localization of UNC-45A with NMII in NK cells and neurons [17,19,20] as well work from Drs. Lappalainen and Chadli's groups were all done using formaldehyde fixation because that is the preferred method for studying the actomyosin system.…”
Section: Discussionmentioning
confidence: 99%
“…For UNC-45A silencing and overexpression scramble and UNC-45A shRNAs lentiviral supernatant or empty vector control and UNC-45A-GFP lentiviral supernatants were prepared and used to infect RFL-6 cells as we have previously described [11,12,22]. For ectopic expression, RFL-6 or U2OS cells were infected with lentiviral particle carrying FLAG only (control) or FLAG-tagged UNC-45A WT, deltaN and deltaC and expression levels were evaluated 24-or 48-hours post infection.…”
Section: Modulation Of Unc-45a and Katanin Expression Levels In Cellsmentioning
confidence: 99%
“…We and others have shown that in mammalian cells, UNC-45A binds to and co-localizes with Non-Muscle Myosin II (NMII) [11][12][13] and the C-terminal NMII-binding domain of UNC-45A is required for myosin II folding, myosin II binding with actin [14,15], and stress fiber assembly [16]. This includes studies from our laboratory showing that UNC-45A plays a role in regulating NMII-assisted functions including cytokinesis [13], exocytosis in immune cells [11], axonal growth of neurons [17] and tunneling nanotube formation [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation